MEANS OF RHETORICS IN THE ANTHOLOGY OF POETRY WORKS OF NATIONAL CHILDREN FROM PAPUA - Razali Razali; Lina Sundana; Novita Rahmayani (Prosiding Seminar Nasional dan Internasional HISKI, 2020)
This study aims to describe the rhetorical tools of children’s poetry, including figures of speech, imagery, and structural manipulation in the Poetry Anthology of the Nation’s Children from Papua. The research method used in this research is qualitative, with descriptive research type. The data source of this research is the Anthology of Poetry by the Nation’s Children from Papua. The data of this research were in the form of rhetorical tools on poetry in Anthology of the Children of the Nation from Papua. The data collection technique used the document analysis technique. The results of the study are as follows. First, the figure of speech used in the anthology is very good, according to the characteristics of children’s poetry. This can be seen from the use of personification figures, metaphorical figures, and simile figures. Second, the use of imagery is also very good and in accordance with the characteristics of children’s poetry. This can be seen from the use of visual images, auditory images, motion images, tactile images, olfactory images, and tasting images. Third, the use of structural manipulation is also very good and in accordance with the characteristics of children’s poetry. This can be seen from the use of repetition, parallelism, anaphora, antithesis, alliteration, climax, and rhetorical questions.